The Urgency of Abu Yusuf's Economic Thoughts in the Stretch of Contemporary Sharia Economic Law - Mugni Muhit; Yadi Janwari; Ahmad Hasan Ridwan (al-Afkar, Journal For Islamic Studies, 2023)
It is believed that Abu Yusuf is a Muslim scholar, Islamic economic thinker who has made a large and significant contribution to the development of modern Islamic economics. He has introduced the basic principles of Islamic economics as contained in his writings on taxes, tax collection administration, infrastructure improvements and the concept of price that goes beyond the concept of price in theory from Adam Smith in his work The Wealth of Nations. Abu Yusuf also discussed several measures for economic development and community welfare. No less important, the basic paradigm and topic of Abu Yusuf's economic thinking is more tendentious towards the responsibility of the ruler towards his people. This is in line with the rule: تصرف اللأمام على الراعيته منوت بالمصلحة And Kitab al-Kharaj is authentic physical evidence of the existence of Islamic public finance, which existed earlier than today's conventional economic theories.